Population Aging and Spatial Dislocation of Pension Service Resource Allocation in Chongqing Metropolitan Area - Wei Xin; Yin Ke (Redai dili, 2022)
As population aging continues to diverge with spatial and temporal evolution, problems such as mismatches between the elderly population and elderly service resources, inadequate utilization, and unreasonable planning layout are increasingly highlighted, and scientific planning for the allocation of elderly service resources is pertinent. Revealing the coordinated relationship and driving mechanism between population aging and elderly service resource allocation at the current stage is the first step in formulating and implementing the plan. Therefore, this study considers Chongqing's main city metropolitan area, where the demand for elderly services is relatively strong, as its research object. Based on the data from the seventh population census and the current regional planning of Chongqing, the study area was divided into the central city and the main city new area, based on which the population aging coefficient and the number of the elderly population were used to analyze the spatial distribution characteristics of population aging in the Chongqing's main city metropolitan area and construct a comprehensive index of elderly service resource allocation. Combined with the Thiel index to explore the balanced characteristics of elderly service resource allocation, the spatial mismatch index and Geodetector were used to explore and analyze the spatial mismatch phenomenon and driving mechanism of population aging and elderly service resource allocation in the study area. The results show that, first, the spatial distribution characteristics of the population aging coefficient and the size of the elderly population in the main city metropolitan area of Chongqing in 2020 are consistent, showing the characteristics of a circular structure decreasing from the inner central city to the outer main city new area. Second, the spatial distribution of the elderly service resource allocation in the main city metropolitan area of Chongqing in 2020 is uneven, with the central urban area forming a hotspot for elderly service resource allocation evaluation, while the main city new area forms a low-value ring for elderly service resource allocation evaluation. Third, there is a spatial mismatch between population aging and elderly service resource allocation in the Chongqing's main urban metropolitan area in 2020, and the contradiction between excess resources in the central urban area and insufficient resources in the new urban area is prominent. Fourth, regional differences in government policies, residents' income levels, population structure, and industrial structure significantly affect the coordinated development of senior care service resources, while the expansion of the market economy, the shrinking of household size, and the intensification of population aging fail to effectively promote the coordinated development of senior care service resources. This study explores the intrinsic connection between population aging and elderly service resource allocation and its driving mechanism from a matching perspective. It provides a scientific basis for promoting the coordinated development of population aging and elderly service resource allocation.